Targeting the epigenome and tumor heterogeneity: advances in immunotherapy for chemoresistant metastatic colorectal cancer - Cao, Yu; Beeraka, Narasimha M.; Efetov, Sergey K.; Liu, Zheng; Otabekov, Akmalbek A.; Basappa, Basappa; Wang, Wensheng; Ma, Dan (Frontiers in Immunology, 2025)
Mitochondria are pivotal organelles that regulate oxidative phosphorylation (OXPHOS). Although microsatellite-stable colorectal cancer represents the majority of CRC cases, the functional aspects of mitochondrial DNA copy number alterations in its progression remains poorly explored. The aim of this review is to explore the mitochondrial mutations associated with CRC and metastatic chemoresistant CRC, alongside mitoepigenetic mechanisms involved in tumor progression and resistance to therapy, with ultimate goal of identifying novel therapeutic strategies. We explored several key areas of mitochondrial biology in CRC (1) mtDNA mutations and cancer metastasis: Understanding how specific mutations in mtDNA drive metastasis in CRC, and their potential role as prognostic markers or therapeutic targets. (2) Mitochondrial copy number variations (CNVs) in CRC (3) Mitochondrial genome and CRC risk revealing links between inherited and somatic mtDNA mutations with CRC susceptibility. (4) ND gene mutations in CRC. (5) Mitoepigenetics in CRC: We highlight how epigenetic dysregulation contributes to CRC progression and chemoresistance. (5) clinical epigenetics in CRC: We described into the role of histone-modifying enzymes, such as EZH2, EP300/CBP, and PRMTs, as drivers of colorectal tumorigenesis by altering transcriptional programs involved in cell proliferation and metastasis. In parallel, this review emphasizes the promising advances in epigenetic-targeted therapies. The dysregulation of epigenetic machinery in cancer offers unique opportunities for therapeutic intervention. Histone acetyltransferases (HATs) like EP300/CBP, histone methyltransferases (HMTs) such as EZH2, and protein arginine methyltransferases (PRMTs) are emerging as critical players in CRC, making them attractive therapeutic targets. The development of selective inhibitors for these epigenetic writers, readers, and erasers, including novel compounds targeting specific protein domains, holds the potential to mitigate tumor growth and overcome resistance mechanisms. Ultimately, the goal is to develop effective synthetic drug scaffolds as immunotherapy treatments for mutation-driven metastatic CRC through pharmacological modeling, combined with targeted chemical inhibitors of CRC-causing epigenetic protein through genome-editing techniques, offering hope for overcoming chemoresistance and improving survival outcomes. Emerging preclinical/clinical insights into mitochondrial dynamics, m6A-mediated transcript regulation, and immune–metabolic signaling in chemoresistant colorectal cancer highlight the translational potential for designing rational synthetic drug scaffolds that modulate validated molecular targets, paving the way for next-generation precision therapeutics.